2017
DOI: 10.1111/1742-6723.12915
|View full text |Cite
|
Sign up to set email alerts
|

Major haemorrhage fatalities in the Australian national coronial database

Abstract: Major bleeding fatalities occurred across a diverse range of contexts, with trauma and gastrointestinal bleeding accounting for most deaths. The majority of patients did not survive to reach hospital. Major haemorrhage occurring entirely outside hospital may be underrecognised from analyses of datasets based primarily on traumatic or in-hospital bleeding. These findings have implications for management of pre-hospital resuscitation and development of clinical practice guidelines for identification and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…As discussed above, there is increasing evidence that the early intervention with blood products has a positive impact on survival in massively bleeding patients. This survival benefit is important when comparing the 0.3% overall risk of alloimmunization and fetal death to the fact that more than half of civilian preventable prehospital deaths are due to hemorrhage, approximately 85% of the 30,000 preventable deaths that occur every year in the United States happen before the patient arrives at the hospital; while in Australia, 69% of people whose major bleeding began in the community did not survive until hospital arrival …”
Section: Positive or D Negative? What's The Risk?mentioning
confidence: 99%
“…As discussed above, there is increasing evidence that the early intervention with blood products has a positive impact on survival in massively bleeding patients. This survival benefit is important when comparing the 0.3% overall risk of alloimmunization and fetal death to the fact that more than half of civilian preventable prehospital deaths are due to hemorrhage, approximately 85% of the 30,000 preventable deaths that occur every year in the United States happen before the patient arrives at the hospital; while in Australia, 69% of people whose major bleeding began in the community did not survive until hospital arrival …”
Section: Positive or D Negative? What's The Risk?mentioning
confidence: 99%
“…Furthermore, the cases in the ANZ‐MTR relate only to patients who reached hospital and received a MT there. In a recently published study of major haemorrhage‐related fatalities reported to the coroner, GIB accounted for 28% of all such deaths, of which only 13% survived to reach hospital and/or receive any transfusion .…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially important difference is the location of the patient at onset of bleeding, which for trauma patients is nearly always outside of hospital. However, the onset of fatal bleeding from GI haemorrhage and ruptured aneurysms commonly occurs at home (Gipson et al, ), and onset of other types of bleeding, such as surgical, nearly always occurs in hospital (Gipson et al, ; Mesar et al, ). These inherent differences pose challenges for introducing MT protocols that can be universally applied and for the management of out‐of‐hospital MT.…”
Section: Blood Component and Coagulation Factor Supportmentioning
confidence: 99%